Hermeneutic Approach as a Condition of Training Future Teachers of Vocational Training to Use Application Software - E. Y. Neupokoyeva (Научный диалог)
The relevance of the study is that currently the communication component of pedagogical activity is closely connected with information technologies. The author believes that the success of the educational process in general depends on the efficiency of participation in communication. Means of creating conditions for training future teachers of vocational training to solve didactic problems linked with the use of a personal computer in the area of subject specialization is revealed. The author makes a review of publications that concern this issue and identifies the problem area, which formed the basis of the hypotheses of the study. The novelty of the research lies in the fact that the creation of these conditions applies, among others, the hermeneutic approach. The use of hermeneutic approach in the analysis and adaptation of semantic constructs of the conceptual apparatus of information technologies to the tasks of the educational process is discussed. The influence of the level of conceptual apparatus on the formation of custom algorithms in students when working with software packages is emphasized. The definitions of the terms “custom algorithm,” “hermeneutic approach to the study of information technologies” are given. The results of experimental work conducted in this direction are described. The contents of this document may be useful for teachers implementing the program of preparation of bachelors of vocational training (on branches).